Pengaruh Upah Minimum, Tingkat Pendidikan, Inflasi Dan Covid-19 Terhadap Penyerapan Tenaga Kerja Kabupaten/Kota Provinsi Bali - Nyoman Trianka Arisandi; I Komang Gde Bendesa (Universitas Dian Nuswantoro, 2022)
Absorption of labor is one of the important factors in overcoming the problem of unemployment and to support economic development that is being carried out by developing countries in order to create equitable economic development. The research locations are in the districts/cities of Bali Province with secondary data obtained from the publications of the Central Bureau of Statistics (BPS). The number of observations in this study were 108 observations with a period of 12 years and involved 9 regencies/cities of Bali Province using the observation method, as well as using descriptive analysis techniques and panel data regression analysis. The results of the panel data regression test show that the most appropriate chosen model is the random effect model (REM). The results of the study found that the minimum wage, level of education, inflation and Covid-19 have a simultaneous effect on employment in districts/cities of Bali Province. Partially the minimum wage variable has a positive and significant effect on employment absorption in districts/cities of Bali Province. The level of education and inflation have no positive and insignificant effect, and Covid-19 has a significant effect on employment in districts/cities of Bali Province.